Factores de riesgo asociados a la neumonía en los pacientes adultos mayores que acuden al hospital básico Yantzaza, año 2015 - ALVARADO AVILEZ, SHIRLEY BEATRIZ (2016)
This research work was to determine the risk factors associated pneumonia in older adults who attend the Basic Yantzaza Hospital, 2015. For complimend the following methodology is proposed: descriptive, transversal, literature and field, to determine the sociodemographic characteristics of the survey technique was used with the instrument the questionnaire, obtaining as a result that more patients are the 71 to 90 years with 58.33%, female with 55,00%, of rural origin with 58,00%, low socioeconomic status with 68,00%, marital status married to 45.00%. As for the risk factors associated with pneumonia, 58.33% live in overcrowded conditions; 16.67% of people smoke; 28.33% consuming alcohol, 60.00% are dedicated to agriculture as an occupation, and 100% represent all people suffer from chronic degenerative diseases such as diabetes more hypertension with 40.00% kidney disease with 13.33%. The author implemented an intervention plan, aimed at reducing risk factors that contribute to the pneumonia for which it was conducted, educational activities on prevention, treatment, causes and risk factors associated with pneumonia, home visits was conducted to older adults where it was shown on breathing exercises, healthy eating, cleaning and household ventilation, in addition to vaccinating seniors. It is concluded that the risk factors associated with pneumonia are highest percentage on: overcrowding, smoking, alcoholism, chronic degenerative diseases.